2019
DOI: 10.1002/iju5.12058
|View full text |Cite
|
Sign up to set email alerts
|

Amrubicin is effective against small cell carcinoma of the prostate as a second‐line chemotherapeutic agent: A case report

Abstract: Abbreviations & Acronyms AC = adenocarcinoma ADT = androgen deprivation therapy ALP = alkaline phosphatase AMR = amrubicin CAB = combined androgen blockade CE = carboplatin and etoposide CI = carboplatin and irinotecan CMR = complete metabolic response CT = computed tomography FDG = fluorodeoxyglucose GS = Gleason score OS = overall survival PE = cisplatin and etoposide PET = positron emission tomography PI = cisplatin and irinotecan ProGRP = pro-gastrinreleasing peptide PSA = prostate-specific antigen RP = ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…AMR is an inhibitor of DNA topoisomerase II. A phase II trial demonstrated that AMR exerted significant activity against refractory or relapsed SCLC after platinumbased chemotherapy (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Second-line Systemic Therapy For Nepcmentioning
confidence: 99%
See 1 more Smart Citation
“…AMR is an inhibitor of DNA topoisomerase II. A phase II trial demonstrated that AMR exerted significant activity against refractory or relapsed SCLC after platinumbased chemotherapy (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Second-line Systemic Therapy For Nepcmentioning
confidence: 99%
“…In a total of 12 NEPC patients, including 2 cases reported by our group, who had been treated with AMR were identified in the literature (23)(24)(25)(26)(27)(28). First-line therapies for these patients were etoposide plus platinum (N=10) and cisplatin plus irinotecan (N=2).…”
Section: Second-line Systemic Therapy For Nepcmentioning
confidence: 99%
“…Furthermore, in a phase-II GETUG P01 for 60 mCRPC patients with visceral metastases or elevated NE markers, carboplatin/etoposide revealed 8% PSA response, 9% OR of measurable disease, 2.9 months median PFS, and 9.6 months median OS [ 119 ]. Other regimens include cisplatin/irinotecan, carboplatin//irinotecan, gemcitabine/docetaxel/carboplatin, doxorubicin/cisplatin/etoposide, amrubicin, and everolimus [ 120 , 121 , 122 , 123 , 124 ]. Summarizing the data, the survival time is generally reported to be 7–16 months, indicating that the NEPC prognosis and aggressive/anaplastic mCRPC are very poor [ 11 , 125 , 126 ].…”
Section: Neuroendocrine Prostate Cancer (Nepc)mentioning
confidence: 99%